Toplumsal yabancılaşmanın sinemaya yansıması : hayat bazen - Hakverdi, Cem (My University, 2018)
Bu çalışma kent yaşamının yarattığı baskından yorulup sakin, sağlıklı ve güvenli bir yaşam sürebilmenin arayışıyla kırsala yerleşen genç bir çiftin düşledikleri hayata geçiş sürecini görünür kılmayı amaçlayan bir belgesel çalışmadır. Karakterlerin İstanbul’dan ayrılmadan önceki son 4 ayı ile Bozcaada’daki 2,5 yıllık bir dönemi kapsayan çalışma, kent ve kırsal yaşamın pratiğine ilişkin bir takım soruların yanıtlarını arama çabasıyla hazırlanmıştır. yabancılaşma, kentleşme, kırsal yaşam, insan-doğa ilişkisi, iç göç

This research is a documentary work about the moving process of a young couple who felt worn out by the stressful urban life. The couple decides to move to the rural area, Bozcaada, in pursuit of the calmer, healthier, and more secure life they dreamed of having. The documentary draws from the last four months of the characters in İstanbul before moving, and two and a half years of their lives in Bozcaada after moving.It addresses the complex relationship between the practices of rural and urban lives.
Keywords: Alienation (Social psychology) in motion pictures; emigration; human-nature relationships; Istanbul; iç göç alienation; insan-doğa ilişkisi; İstanbul; kentleşme; kırsal yaşam; Köyden kente göç, Sinemada; Motion pictures; rural life; Rural-urban migration in motion pictures; Sinema; Turkey; Türkiye; urbanization; yabancılaşma; Yabancılaşma (Sosyal psikoloji), Sinemada